Time-dependent Photoionization Modeling of Warm Absorbers: High-resolution Spectra and Response to Flaring Light Curves - Dev R. Sadaula; Timothy R. Kallman (The Astrophysical Journal, 2024)
Time-dependent photoionization modeling of warm absorber (WA) outflows in active galactic nuclei can play an important role in understanding the interaction between WAs and the central black hole. The WA may be out of the equilibrium state because of the variable nature of the central continuum. In this paper, with the help of time dependent photoionization modeling, we study how the WA gas properties change with time and how it reacts to changing radiation fields. Incorporating a flaring incident light curve, we investigate the behavior of WAs using a photoionization code that simultaneously and consistently solves the time-dependent equations of level population, heating and cooling, and radiative transfer. We simulate the physical processes in the gas clouds, such as ionization, recombination, heating, cooling, and the transfer of ionizing radiation through the cloud and present high-resolution time-resolved absorption spectra. We demonstrate that time-dependent radiative transfer is important and the calculations that omit this effect quantitatively and systematically underestimate the absorption. Time-dependent photoionization models provide crucial insights into the characteristics of WAs and can be used to constrain their density and spatial distribution.